Oncology Comparative Effectiveness Research: A Multistakeholder Perspective on Principles for Conduct and Reporting. (6th May 2013) - Ramsey, Scott D.; Sullivan, Sean D.; Reed, Shelby D.; Tina Shih, Ya‐Chen; Schaecher, Ken; Dhanda, Rahul; Patt, Debra; Pendergrass, Kelly; Walker, Mark; Malin, Jennifer; Schwartzberg, Lee; Neumann, Kurt; et al.
Learning Objectives: Compare well‐conducted CER and phase I‐III clinical trials. Describe barriers to the acceptance of CER studies by the oncology community. Demonstrate the use of CER for decision‐making in oncology. Abstract : Comparative effectiveness research (CER) can assist patients, clinicians, purchasers, and policy makers in making more informed decisions that will improve cancer care and outcomes. Despite its promise, the factors that distinguish CER from other types of evidence remain mysterious to many oncologists. One concern is whether CER studies will improve decision making in oncology or only add to the massive amount of research information that decision makers must sift through as part of their professional responsibilities. In this report, we highlight several issues that distinguish CER from the most common way evidence is generated for cancer therapy—phase I–III clinical trials. To identify the issues that are most relevant to busy decision makers, we assembled a panel of active professionals with a wide range of roles in cancer care delivery. This panel identified five themes that they considered most important for CER in oncology, as well as fundamental threats to the validity of individual CER studies—threats they termed the "kiss of death" for their applicability to practice. In discussing these concepts, we also touched upon the notion of whether cancer is special among health issues with regard to how evidence is generated and used. Abstract : Comparative effectiveness research (CER) can assist patients, clinicians, purchasers, and policy makers in making more‐informed decisions that will improve cancer care and outcomes. However, the factors that distinguish CER from other types of evidence remain mysterious to many oncologists. This article reports on a panel of oncology professionals who identified five themes that they considered most important for CER in oncology, as well as fundamental threats to the validity of individual CER studies. Abstract : 摘要 比较效益研究（CER）有助于患者、临床医生、费用支付者和政策制定者制定更为明智的决策用于改善癌症的治疗和结局。尽管CER前景良好，但很多肿瘤学家仍不清楚CER和其他类型证据之间的区别。一种顾虑是，CER研究能否改善肿瘤学决策的制定？还是仅仅添加了大量的研究信息（而研究者出于专业责任必须仔细查看这些信息）？在本报告中我们突出强调了CER与最常见癌症治疗证据形式——I ∼ III期临床试验——之间的数项区别。为帮助工作繁忙的决策制定者确定哪些问题最为相关，我们召集了在肿瘤治疗服务中发挥各种不同作用的活跃的专业人士组成一个讨论组。该小组确定了他们所认为在肿瘤学CER中最为重要的5个主题，同时确定了对于一项CER研究效度而言最根本的威胁——他们把这些威胁称为在临床实践中适用性的"死亡之吻"。在讨论这些概念时，我们也提及了关于如何生成和使用证据方面，癌症是否需要特殊对待的问题。 The Oncologist 2013;18:760–767